New species and new records of cumaceans (Crustacea: Peracarida: Cumacea) from the Andaman Islands, Indian Ocean - Petrescu, Iorgu; Chatterjee, Tapas (Zootaxa, 2011)
This paper describes a collection of Cumaceans from intertidal macroalgae on the shores of the Andaman Islands containing two new species viz. Bodotria andamanensis sp. nov. of the family Bodotriidae, Gynodiastylis bacescui sp. nov. of the family Gynodiastylidae and five species of the family Nannastacidae of which three species viz. Cumella forficuloides Băcescu & Muradian, 1975, Nannastacus goniatus Gamô, 1962 and Scherocumella nichollsi Hale, 1945 are recorded for the first time from India. Bodotria andamanensis sp. nov. is characterized by having two large visual elements, the first segment of the pereon hardly visible dorsally, maxilliped 3 with robust articles, a short uropod, rami with two articles; Gynodiastylis bacescui sp. nov. is characterized by an elongated carapace, a rounded and large telson, reaching half of the length of the uropodal peduncle, the basis of maxilliped 3 with a short outer plumose seta, and a uropodal endopod with three articles.